1998
DOI: 10.1161/01.cir.98.19.1990
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Hypoxia Elevates Skeletal Muscle Interstitial Adenosine Levels in Humans

Abstract: Background-Adenosine is a potent vasodilator that has been shown to increase in cardiac tissue in response to hypoxia.However, peripheral vasodilatation also occurs during hypoxia, and the vasoactive substance(s) responsible for skeletal muscle vasodilation have not yet been completely identified. Therefore, the purpose of this study was to measure and quantify skeletal muscle interstitial adenosine during acute systemic hypoxia. Methods and Results-Skeletal muscle interstitial adenosine concentrations were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
46
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 19 publications
(23 reference statements)
6
46
1
Order By: Relevance
“…Because hypoxia raises sympathetic vasoconstrictor nerve traffic and norepinephrine spillover (14,31), vasodilation results from release of systemic or local vasodilator factors. In agreement with studies in rodents (22,24,26), it has been reported that nitric oxide (NO) (7,9,16,35) and adenosine (15,18) contribute to hypoxiainduced vasodilation in humans. In addition, some reports (6,35), but not others (27), support a role for an increase in circulating epinephrine, and one recent report (19) suggests that vasodilator prostaglandins also contribute to the skeletal muscle vasodilation elicited by systemic hypoxia.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Because hypoxia raises sympathetic vasoconstrictor nerve traffic and norepinephrine spillover (14,31), vasodilation results from release of systemic or local vasodilator factors. In agreement with studies in rodents (22,24,26), it has been reported that nitric oxide (NO) (7,9,16,35) and adenosine (15,18) contribute to hypoxiainduced vasodilation in humans. In addition, some reports (6,35), but not others (27), support a role for an increase in circulating epinephrine, and one recent report (19) suggests that vasodilator prostaglandins also contribute to the skeletal muscle vasodilation elicited by systemic hypoxia.…”
supporting
confidence: 80%
“…In a series of studies, Marshall and collaborators demonstrated that adenosine, NO, and vasodilator prostaglandins each contribute to the skeletal muscle vasodilation induced by hypoxia in rodents (20,24,26). In an extension of these studies in humans, NO (7,9,35) and adenosine (15,18,24) have also been shown to play a role in the hypoxia-induced vasodilation in humans. It has also been shown that vasodilation during hypoxia can result from reduction of nitrite to NO as a function of local PO 2 (10).…”
Section: Discussionmentioning
confidence: 98%
“…In the brain, adenosine exerts an inhibitory tone and serves as an endogenous neuroprotective agent against ischemia-and seizure-induced neuronal injury (Rathbone et al, 1999;Latini and Pedata, 2001). In the skeletal muscle, adenosine functions as a locally produced regulator of muscle blood flow and plays a major protective role during systemic hypoxia (Hellsten et al, 1998;MacLean et al, 1998). Our quantitative PCR results showed that hENT1 is highly expressed in both human brain and skeletal muscle (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Adenosine, a potent vasodilator, has been demonstrated to increase in skeletal muscle and contribute to vasodilation in response to systemic hypoxia (18,19). Endothelium-derived prostaglandins also have a clear role in modulating skeletal muscle vasodilation in response to hypoxia (20).…”
Section: Discussionmentioning
confidence: 99%